La morphologie des environs de Québec et la basse-vallée du Saint-Laurent - Taillefer, François (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1958)
The morphology of the Québec region and the lower St. Lawrence valley is reappraised in this article divided in three parts. The physical landscape is described in part I ; the structural conditions are examined in part II and the morphological problems are presented in part III.The relief is the result of a succession of glacial episodes and submersion and emersion episodes which followed glaciation. The over deepening of the Limoilou depression and the opening of Calvaire lake and Cap Rouge depressions are the results of the glacier. To the submerged phase correspond the alluvial fill, especially thick in the Limoilou depression, and during the emersion phase, the St. Lawrence cut in soft schists the Ancienne Lorette and the lower terrace which would have been shaped after the over deepening of the Limoilou depression.